TINJAUAN MAQASID SYARI’AH TERHADAP PENCATATAN PEKAWINAN - Tenggo Subangun Harahap (IAIN BONE, 2023)
The Indonesian Muslim community is still faced with the problem of two understandings of marriage registration. First, the registration of marriages is considered a legal requirement for marriage, so that unregistered marriages (sirri) are considered as marriages that have no legal force. The provisions for the obligation to register a marriage are contained in Law no. 1 of 1974 Article 2 paragraph (2); jo. Articles 4 and 5 KHI. Second, the understanding that judges that even without marriage registration, the marriage is considered valid according to religious law, if the fiqh requirements and harmony are met, this opinion also rests on Law No. 1 of 1974 Article 2 paragraph (1), which restores the validity of marriage based on each religious law. This article aims to reaffirm the position of registering marriage as a necessity when viewed from the perspective of maqasid shari'ah. This study uses a qualitative normative approach, with secondary data sourced from searching books, laws, and various related literature. The results of the study show that the status of marriage registration is purely the result of ijtihad, and in essence it is in line with the goals of syara' and does not violate the benefit, namely the maintenance of religion and lineage by creating an orderly administration. Likewise, the maintenance of human assets in the context of marriage, because with legal force, a marriage can anticipate the implications of a legal action.